Integrating happiness research into endpoint indicators of social life cycle analysis - Mann, Stefan (Managing global transitions, 2025)
Endpoint indicators for social life cycle analysis (S-LCA) are still less consolidated than those for environmental LCA. There is a broad consensus that human well-being should be the overarching goal of social sustainability and therefore also of S-LCA. However, to date the two major databases for S-LCA are restricted to a multiplication of working hours with a quality- or risk-adjusted factor. This paper aims to evaluate the congruence between this technical pragmatism and well-established findings of happiness research. The analysis starts with the argument that evidence and consequentiality are necessary criteria for any variables used. It is then shown that some of the variables such as poverty are not consequential, while the unit of working hours lacks any evidence about a relationship with subjective well-being. The analysis concludes that a simple pointbased endpoint indicator would be more appropriate for S-LCA than the current hour-based indicator.
Keywords: analiza življenjskega cikla; družbena trajnost; endpoint; indicators; kazalniki; končni kazalnik; life cycle analysis; social sustainability